The Influence of the Quantity of Memorizing Surahs and Muroja'ah Al-Qur'an on Students' Cognitive Learning Outcomes - Sari, Sulistya Umie Ruhmana; Ningrum, Alia Putriana; Adynastiti, Mahsa Nabilah; Laili, Iftitah Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to identify whether there is an influence between the quantity of memorization of the Quran and muroja'ah on students' cognitive learning outcomes using regression analysis with the independent variables being the quantity of memorization of the Quran  and the quantity of muroja'ah  and the dependent variable being students' cognitive learning outcomes . Most previous studies only highlight the effects of memorization on general aspects such as improving learning outcomes, without specifically measuring the impact of the quantity of memorization and the intensity of muroja'ah on students' cognitive learning outcomes. This study attempts to fill this gap by analyzing the relationship between memorization of the Quran and academic achievement in more depth. The sample used was 50 6 th semester students spread across various study programs at FITK UIN Maulana Malik Ibrahim Malang. Sampling was carried out randomly with the assumption that the characteristics of the students were homogeneous. The results of the study showed that 80% of students had memorized 30 surahs in Juz 30, and on average they did the muroja'ah memorization 7 times a week. For the dependent variable, the average GPA obtained by students is 3.85. In the results of the hypothesis test, the F-count value is 10.93 and the significance value is 0.001 with an alpha setting of 0.05. So, it can be concluded that H0 is rejected so that there is at least 1 independent variable that influences students' cognitive learning outcomes, then the results of the partial test showed that the quantity of memorizing the surah of the Qur'an affects students' cognitive learning outcomes with a significance value of 0.004 which is smaller than 0.05. The quantity of memorizing the surah of the Qur'an affects learning outcomes with an R 2 value of 46% and the remaining 54% is influenced by other factors not used in this study. For educators and curriculum developers, they can integrate memorization techniques into the curriculum, develop a supportive learning environment, and utilize educational technology to increase student motivation and involvement in the learning process.